PENGARUH SIMPANAN, PEMBIAYAAN DAN MODAL TERHADAP LABA PADA BTM WAHANA MENTARI KABUPATEN INDRAGIRI HULU - Angga Hapsila (LPPM Press STIE Indragiri Rengat, 2018)
The research was conducted by the writer on BTM Mentari in sub districts rengat - indragiri upstream. District. The research phase lasting three months. This research study is to find savings, influence financing and capital to profit in the district btm mentari Indragiri upstream. This research used secondary data , writer process data by using multiple linear regression the it using spss ( statistic package for social scince ) 24 version to get output to summarizing the research. The research that is simultaneously a conclusion can be drawn is the significant savings, between financing and capital to profit. This can be seen that the f count greater than the f table ( 29,873 > 2,36 ) When viewed from the table a model summary so r which means a correlation coefficient obtained value of 0,984 which means the amount of savings mobilized , the financing of the and capital had strong ties against spider does not permit the .Was in the middle of the value of the coefficients detrminasi as much as 0,968 paper work showing that the amount of savings mobilized , the financing of the and capital affect of the spider that has been accepted by the BTM the spacecraft mentari as much as 96,80 % the remaining of 3,20 % influenced by the fact that of other variables that do not writer you wherever you may be.